Varicocelectomy's Impact on Semen Analysis in Infertile Patients (المجلة الدولية للبحوث العلمية, 2023)
This study aimed to evaluate the effects of open subinguinal varicocelectomy on sperm parameters in infertile men. Results: The study included 70 patients with varicocele who underwent the surgery, and significant improvements were observed in semen parameters, including volume, concentration, count, motility, and morphology. Additionally, there was an increase in the likelihood of achieving pregnancy after surgery. Unilateral varicocelectomy had a greater impact on improving these parameters than bilateral varicocelectomy. Furthermore, undergoing the surgery at a younger age had a more significant impact. The mean age of patients was 27 years old, with all being married; unilateral varicocele was found in 71% of cases, while the remaining cases presented as bilateral; duration of infertility averaged around one year for all participants, with primary infertility accounting for most cases (87%). Varicocele grade II occurred among approximately one-third (34%) of participants, while grade III occurred among two-thirds (66%) of participants. No intra-operative complications were reported during or after surgeries that involved routine preoperative investigations such as physical examination and color Doppler ultrasound, along with hormonal profile analysis, before scheduling open subinguinal conventional varicocelectomies. In conclusion, this prospective descriptive study showed that subinguinal varicocelectomy improves patients' semen quality by increasing volume, concentration, count, motility, and morphology. All differences mean an increase in all parameters (volume = 0.7 ml, count = 13 million/mL, motility = 12%, and achievement of pregnancy (no = 16, 22.9%), leading to higher chances of achieving pregnancy. This effect is greater when performed unilaterally (n = 45,64.3%) than bilaterally (n = 18,25.7%), especially if done at younger ages, but further studies are needed to confirm these findings using larger sample sizes.